2018
DOI: 10.21037/gs.2018.07.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CT angiography and venous couplers on surgery duration in microvascular breast reconstruction: a single operator’s experience

Abstract: Background: The use of CT angiography (CTA) or venous couplers (VCs) has led to shorter operative times in free flap breast reconstruction (FFBR). However, there are no reports on the effect of these two interventions relative to each other or combined.Methods: Abdominal based FFBRs performed by a single surgeon before introduction of either intervention were compared to those with VC only, and those after the addition of CTA to VCs (CT-VC).Operative time was defined as from "knife-to-skin" to insertion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…11,12 For example, prior studies that have demonstrated a decrease in operative time have examined patient groups before and after the routine implantation of CTA prior to DIEP flap surgery, and are thus subject to potential bias from a surgical learning curve as the surgical team gains more experience. 13,14 Routine CTA was not implemented in our study cohort and was only utilized by the surgeon when there was a specific concern about the location or patency of the DIEP vessels given a patient's history. Even among patients with prior abdominal scars, preoperative CTA was utilized in only 16.8% of patients in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 For example, prior studies that have demonstrated a decrease in operative time have examined patient groups before and after the routine implantation of CTA prior to DIEP flap surgery, and are thus subject to potential bias from a surgical learning curve as the surgical team gains more experience. 13,14 Routine CTA was not implemented in our study cohort and was only utilized by the surgeon when there was a specific concern about the location or patency of the DIEP vessels given a patient's history. Even among patients with prior abdominal scars, preoperative CTA was utilized in only 16.8% of patients in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, flap failure was not associated with venous thrombosis underlining the superiority of venous coupler systems compared to handsewn anastomoses (23,30,36). As a preliminary finding, the combination of venous coupler anastomosis and preoperative CTA is a valuable tool to enhance the safety of autologous breast reconstruction using abdominal free flaps (37).…”
Section: Discussionmentioning
confidence: 86%
“…Pre-operative CT angiography has helped predict the chance of success with a DIEP flap reconstruction by identifying candidate perforators and conversely indicating those patients who are technically unsuitable for this procedure. The biggest advantage of CT angiography in breast reconstruction has been to speed up the surgery ( 88 ) as it provides an intraoperative roadmap for perforator selection, location and dissection.…”
Section: Autologous Tissue Versus Implant-based Reconstructionmentioning
confidence: 99%